2020
DOI: 10.3390/insects11110795
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Pollinators Foraging on Centipedegrass Inflorescences

Abstract: Turfgrasses are commonly used for lawns and as recreational surfaces in the USA. Because grasses are largely wind-pollinated, it was thought that pollinators would not forage on turfgrasses. Centipede grass (Eremochloa ophiuroides (Munro) Hack) is a warm-season turfgrass widely used in the southeastern USA. Centipede grass produces spike-like inflorescences from August to October, and little is known about whether pollinators utilize those inflorescences as pollen resources. Thus, the objective of the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The current study showed that mowing operations with at least a 14-day interval were sufficient to support fresh floral resources, including white clover, and to attract pollinators. On centipedegrass and bahiagrass, a 14 d mowing gap allowed enough time for the emergence of new spikelets to be available for foraging bees [11,12]. White clover is known to disappear from grassy weed areas over several years [34]; thus, reseeding with white clover is recommended [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study showed that mowing operations with at least a 14-day interval were sufficient to support fresh floral resources, including white clover, and to attract pollinators. On centipedegrass and bahiagrass, a 14 d mowing gap allowed enough time for the emergence of new spikelets to be available for foraging bees [11,12]. White clover is known to disappear from grassy weed areas over several years [34]; thus, reseeding with white clover is recommended [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies showed that different bees visit turfgrass environments [9]. Bees forage on the spikelets of centipedegrass [10,11] and bahiagrass lawns [12]. When allowed to grow out, turfgrass naturally hosts a diverse group of flowering plants, which are mostly referred to as weeds, such as white clover (Trifolium repens L.) and common dandelion (Taraxacum officinale Weber) in the southeastern US [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, pollinators collect pollen from many grasses, including row crops and turfgrasses. In particular, bees and syrphid flies, have been documented collecting pollen from at least 99 grass species [7,9]. Additionally, many insects including Apis mellifera (Hymenoptera: Apidae, honeybee), Spatunomia spp., Patellapis (Zonalictus) sp., Lipotriches sp., Nomia (Acunomia) sp., and Lasioglossum (Evylaeus) sp.…”
Section: Introductionmentioning
confidence: 99%